Co-occurrence of syndrome of horizontal gaze palsy with progressive scoliosis with stroke in young: a case report - Kauser, Mohamed Murtuza; Kamarthy, Prabhakar; Afreen, Asfia; Anjinappa, Raveesha (International Journal of Research in Medical Sciences, 2017)
Horizontal Gaze Palsy with Progressive Scoliosis (HGPPS) is a rare autosomal recessive syndrome of hind brain maldevelopment associated with ocular and skeletal manifestations. To the best of our knowledge there have been no case reports from India although a family of Indian decent has been reported from Saudi Arabia. The clinical and MRI features along with its co-occurrence with stroke in young will be described in this paper.